How to Train Critical Thinking Skills? : Application of Problem-Based Learning Model Lesson Study Pattern - Marhamah Marhamah; Baiq Fatmawati; Sarwati Sarwati; Nunung Ariandani (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to describe the critical thinking skills of biology students through the application of the Problem-Based Learning Lesson Study pattern. The research method used was descriptive qualitative. The subjects in this study were Biology students of semester V at Hamzanwadi University. The research instruments consisted of observation sheets to obtain information about the learning process with Lesson Study patterns, as well as essay test instruments to measure students' critical thinking skills. Critical thinking indicators used include the ability to formulate problems, the ability to provide arguments, deductive ability, inductive ability, and evaluation ability. Data analysis was done descriptively and qualitatively. The effectiveness of applying the problem-based learning model to students' critical thinking skills was assessed using the N Gain formula. Based on the N Gain results, the problem-based learning model was quite effective in improving students' critical thinking skills with the following details; the ability to formulate problems was 0.67 (medium), the ability to provide arguments was 0.42 (medium), deductive ability was 0.44 (medium), inductive ability was 0.40 (medium), and evaluation ability was 0.41 (medium). Meanwhile, the learning process with Lesson Study which includes the Plan, Do, and See stages provides valuable learning for the team of lecturers involved when jointly designing learning, observing learning, and reflecting on learning, followed up in the learning process in the class they teach.